Aislamiento de quercetina de Allium fistulosum L. e identificación mediante espectropia uv-visible y caracterización fisicoquímica - Guerra Trauco, Siomara Geraldine (2024)
Allium fistulosum L. is a species of small onion that grows profusely in the Loreto region and contains quercetin with a broad spectrum of activity as an antioxidant, anti-inflammatory, anticancer, antiarthritic, etc. The objective of the present work was to isolate quercetin and characterize it by measuring its physicochemical and spectrometric parameters. The samples were collected in the town of Zungarococha, district of San Juan Bautista, province of Maynas, region of Loreto. The dry bulb was pulverized and degreased with petroleum ether in Soxhlet equipment, then macerated for 40 hours in 95º ethanol with intermittent agitation, filtered in a Buchner funnel on filter paper, purified with norite and yellow crystals in the form of needles were obtained. The measurements of its physicochemical characteristics showed the following values: melting point 312ºC, Rf in Silicagel 27 and polyamide 8, molecular weight 338.16±0.0225, and color reactions were positive for phenols. UV-visible spectra in methanol were 255, 269 Sh, 301 Sh, and 370nm, in methanol and sodium methoxide 247 Sh, 321nm, and in methanol sodium acetate 257 Sh, 274, 329, and 390nm. The yield was 0.57% and that would allow A. fistulosum L. could be used as an additional source to extract quercetin for pharmacological purposes.